Phosphorylation of the WH2 domain in yeast Las17/WASP regulates G-actin binding and protein function during endocytosis - J. J. Tyler (Nature Portfolio, 2021)
Abstract Actin nucleation is the key rate limiting step in the process of actin polymerization, and tight regulation of this process is critical to ensure actin filaments form only at specific times and at defined regions of the cell. WH2 domains are short sequence motifs found in many different actin binding proteins including WASP family proteins which regulate the actin nucleating complex Arp2/3. In this study we reveal a phosphorylation site, Serine 554, within the WH2 domain of the yeast WASP homologue Las17. Both phosphorylation and a phospho-mimetic mutation reduce actin monomer binding affinity while an alanine mutation, generated to mimic the non-phosphorylated state, increases actin binding affinity. The effect of these mutations on the Las17-dependent process of endocytosis in vivo was analysed and leads us to propose that switching of Las17 phosphorylation states may allow progression through distinct phases of endocytosis from site assembly through to the final scission stage. While the study is focused on Las17, the sole WASP family protein in yeast, our results have broad implications for our understanding of how a key residue in this conserved motif can underpin the many different actin regulatory roles with which WH2 domains have been associated.